PERBUATAN MELAWAN HUKUM MENGENAI PENCABUTAN KUASA OLEH PEMBERI KUASA SECARA SEPIHAK BERDASARKAN PASAL 1814 KUHPERDATA - Alma Rizki Agisti; Temmy Fitria Alfiany (JOURNAL OF LAW AND NATION, 2024)
This research aims to find out the legal consequences of unilateral revocation of power of attorney by the power of attorney grantor and to find out the legal considerations of the judge in deciding Decision No. 2/Pdt.G/2022/PN Skb. The method used in this research is a qualitative method. The type of research used by the author is normative legal research with a Decision Study Approach and a Legislation Approach. The data used in this research is secondary data, which is obtained through the collection of library materials from various sources relevant to the research problem. The data collection methods in this research are literature study and decision study. The results show that the consequences of unilateral revocation of power of attorney by the client can affect the fulfillment of rights and obligations agreed upon in the agreement. If the client as the power of attorney does not fulfill its obligations, this can lead to disputes because the revocation causes losses to the advocate as the recipient of the power of attorney. Losses that can occur include material losses that can be calculated with nominal money, and immaterial losses that cannot be calculated with nominal money. The two losses above when there is a default or unlawful act. As well as the consideration of the panel of judges that the arguments of the plaintiff's exception cannot be accepted because they cannot be proven before the trial.